Combined Hereditary Disorders of Haemophilia B Leyden (-6 G → A) and Type 1 von Willebrand Disease - Pernod, Gilles; Vinciguerra, Christine; Gaucher, Christine; Mazurier, Claudine; Polack, Benoît; Négrier, Claude (Thrombosis and Haemostasis, 1996)
Multiple coagulation disorders are unusual. We report here a combination of haemophilia B Leyden with type 1 von Willebrand disease (vWD) affecting different members of the same family. Haemophilia B Leyden was due to a -6 G → A mutation within the promoter of the factor IX gene and was responsible for a mild haemophilia in the father of the proband. The proband and her sister (age 4 and 6) exhibited a twofold lower level of factor IX activity (0.4 IU/ml) than the paternal grandmother (0.95 IU/ml). The differences in FIX levels in the three carriers of the same -6 G → A mutation suggest the implication of an age-related mechanism responsible for the increase in factor IX plasma level. Haemophilia B Leyden patient and carriers suffered also from a mild von Willebrand disease. The diagnosis of this associated type 1 vWD was performed by assaying plasma von Willebrand factor together with multimer electrophoretic studies and DDAVP test. The inheritance of this vWD was investigated by haplotype analysis of the vWF gene. Individuals affected by such an association are actually asymptomatic, but per- and post-operative bleeding risk remains to be evaluated.